Photothermal Hyperthermia Suppresses Liver Tumor Growth Via Hippo Signaling Pathway-Dependent Inhibition of Cell Proliferation and Induction of Apoptosis - Jian Li; Yuanhua Qin; Yingying Yang; Hang Chen; Mengjuan Li; Yadi Liu; Bingjie Liu; Jingli Shang; Yu Zhang; Tao Han; Yuhan Hu; Feng Ren (Biological Procedures Online)
Abstract Hepatocellular carcinoma (HCC) ranks as the third most common malignant tumor globally. Although hyperthermia has shown promise as a non-invasive treatment for tumors, its specific mechanisms and impact on HCC remain underexplored. This study aims to investigate the effects of hyperthermia on HCC proliferation and apoptosis and to elucidate the role of the Hippo signaling pathway in these processes. Huh7 and HepG2 HCC cells were cultured at various temperatures (37 °C, 40 °C, 43 °C, and 46 °C), with 37 °C as the control. Cell proliferation, apoptosis, and cell cycle distribution were assessed via CCK-8 assays and flow cytometry. A subcutaneous xenograft model in nude mice, treated with indocyanine green (ICG) and near-infrared (NIR) irradiation to achieve local hyperthermia, was used to evaluate in vivo tumor growth. RNA-seq and KEGG pathway analyses identified differentially expressed genes, and Western blotting and immunofluorescence were used to confirm the involvement of the Hippo signaling pathway. Hyperthermia at 43 °C significantly inhibited Huh7 and HepG2 cell proliferation and induced apoptosis, accompanied by cell cycle arrest. In vivo, local hyperthermia reduced tumor volume and weight in the ICG + NIR-treated group. RNA-seq and KEGG analyses revealed that the Hippo signaling pathway was activated under hyperthermic conditions, with YAP expression and nuclear translocation markedly downregulated. Further experiments showed that YAP overexpression mitigated hyperthermia-induced effects on cell proliferation and apoptosis, underscoring the role of the Hippo pathway. These findings demonstrate that hyperthermia inhibits HCC growth by regulating the Hippo signaling pathway, reducing cell proliferation, and promoting apoptosis. This study highlights the potential of hyperthermia as an effective therapeutic approach for HCC, with implications for developing targeted hyperthermic therapies.